Experiments for students with built-in theory: 'PUMA: Spannungslabor' – an augmented reality app for studying electricity. (1st July 2022) - Stolzenberger, Christoph; Frank, Florian; Trefzger, Thomas
Abstract: With the help of augmented reality apps objects and text can be added virtually to the physical world (e.g. physical experiments) in real time. The augmented reality (AR) app 'PUMA: Spannungslabor ' enhances simple electric circuits experiments for students with virtual representations based on the electron gas analogy including visualisations of interior processes in various components such as lamps and resistors. This opens up new possibilities for connecting theory and experiment in secondary school physics teaching. While using the AR app students are enabled to acquire qualitative and semi-quantitative knowledge about the basic concepts of current, voltage, potential, and resistance as well as the laws of series and parallel circuits easier and more directly. This holistic approach of learning through experiments can facilitate a deeper and more interconnected understanding of the topics covered in physics lessons.